Hero As A Literary Concept (Diversity Research: Journal of Analysis and Trends, 2025)
The article explores the evolution and diversity of approaches to defining the concept of «literary hero». Particular attention is paid to the functions of the hero: plot-forming, ideological, psychological and symbolic. The article emphasizes that the study of the hero is not only an analysis of the literary image, but also a dialogue with the historical context, philosophical concepts and the evolution of human self-awareness